From commitment to expressionism: a survey on the changing concept of photography in Iran. Issue 5 (20th October 2022) - Azari Azqandi, Hadi; Fahimifar, Asghar; Sheikhmehdi, Ali
Abstract : This paper examines the evolution of the concept of photography in Iran during the two decades following the 1979 Islamic revolution and its relationship to a changing political discourse during that period. Since the state became a dominant player in culture and the arts during the post-Islamic revolutionary era, this paper puts the evolution of the concept of photography into a socio-political context. Using Discursive Institutionalism as a theoretical framework, we examine Iranian photographers' ideas on photography as well as the discourses that affected photography organisations, revealing the forces driving changes in how photographic work was conceived. The first decade following 1979 the Islamic revolution was marked by eight years of war, and photography was purposed to produce factual documents, leaving no room for picture-making, manipulation or self-expression. Meanwhile due to the revolutionary and leftist agenda set forth by the Mir-Hussein Mousavi administration (1981–1989), photography was formulated as a commitment to depict social deprivation and the difficulties in achieving social reforms. However, with the liberalising ideas introduced during Hashemi Rafsanjani's administration (1989–1997), the concept of photography began to change. Photographic work became less an expression of political commitment to being seen as a form of self-expression that valued formalism and image-making. In other words, the changing political discourses during this period mark a shift from 'taking' to 'making' photographs. The intellectual opening In Iranian society that began in the early 1990s both paved the way for a more theoretical approach to photography as well as growing diversity in the organisation of photographic work. In particular, the more liberal attitude of the Rafsanjani administration resulted in a significant increase in the number of journals, newspapers and publications that provided a market for more imaginative photography, and a fluorescence of picture 'making.'